Unusual Termination of Facial Artery Associated with the Presence of Premasseteric Branch- A Case Report. - Abhinitha P,; Naveen K,; Jyothsna P,; Mohandas Rao KG,; Satheesha NB,; Venumadhav N,; Swamy Ravindra S, (Department of Surgery, UKM Medical Centre, 2014)
Face being highly vascular region essentially receives extensive blood supply from the facial artery. Facial artery frequently shows variation in its pattern of origin, course and termination. An unusual premasseteric branch is the one among its variant branches on the face. We report herewith the untimely termination of facial artery as alar artery at the nose instead of medial angle of the eye associated with an abnormally large posterior branch known as premasseteric branch. Presence of premasseteric artery may be considered as beneficial in ‘raising flap’ approaches. However, ascertaining its existence makes obligatory for the surgeons during surgical procedures of the face.